2009
DOI: 10.1176/jnp.2009.21.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Affective Component of the Cerebellar Cognitive Affective Syndrome

Abstract: The authors performed a systematic review and meta-analysis of studies evaluating the affective component of the cerebellar cognitive affective syndrome. Depressive and anxiety symptoms and personality changes were more frequent in patients with spinocerebellar ataxia. Patients with cerebellar lesions were more likely to have depression, deficits in the ability to experience emotions, and behavioral difficulties. A meta-analysis revealed modestly higher scores on the Hamilton Depression Rating Scale (HAM-D) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(59 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…42 Therefore, a global proteomics analysis on the control and irradiated cerebellum and on cerebellar synaptosomes was performed. This showed similar alterations to signalling pathways as the hippocampus and cortex.…”
Section: Long-term Molecular Consequences Of Ionising Radiation In Cementioning
confidence: 99%
“…42 Therefore, a global proteomics analysis on the control and irradiated cerebellum and on cerebellar synaptosomes was performed. This showed similar alterations to signalling pathways as the hippocampus and cortex.…”
Section: Long-term Molecular Consequences Of Ionising Radiation In Cementioning
confidence: 99%
“…In humans, the cerebellum plays an important role in motor control, and it may also be involved in some cognitive functions such as attention and language as well as in regulating fear and pleasure responses 47 . Functional imaging studies have shown cerebellar activation in relation to language, attention, and mental imagery; correlation studies have shown interactions between the cerebellum and non-motor areas of the cerebral cortex; and a variety of non-motor symptoms have been recognized in people with damage that appears to be confined to the cerebellum 48, 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is a structure attached to the bottom of the cerebral hemispheres of the brain that plays an important role in motor and cognitive functions [1]. Its surface is covered with finely spaced parallel grooves, in striking contrast to the broad irregular convolutions of the cerebral cortex.…”
Section: Anatomy Of Cerebellummentioning
confidence: 99%
“…Hydro alcoholic extracts of pomegranate peels were shown to cause significantly reduced blood glucose level in healthy and diabetic rats [107,108]. (1,2) or (1,6) glucopyranosyl substituents [110]. Barley possesses several medicinal applications.…”
Section: Pomegranatementioning
confidence: 99%